Fire protection system based on the Internet of Things - Valerry; Hambali; Hidayat, Rahmat (Journal of Industrial Automation and Electrical Engineering, 2024)
Fire is a significant threat to life and property safety, especially with the increasing risk due to rapid technological and infrastructure developments. This paper proposes an Internet of Things (IoT)-based fire protection system that utilizes an ESP32 microcontroller for automatic monitoring and response to potential fires. This system integrates various sensors, namely a DHT22 sensor to measure temperature, an MQ-02 sensor to detect hazardous gases, and a fire sensor to identify the presence of fire. When there is an increase in temperature, gas detection, or fire, the system automatically activates devices such as water pumps, fans, and APAR valves that are connected via relays, and sends real-time notifications equipped with location data via the Telegram application. Through this IoT-based approach, the system can be monitored and controlled remotely, providing a fast and effective response in fire mitigation efforts. The implementation of this system is expected to minimize the impact of fires by detecting and addressing potential hazards automatically and in real-time.